Development Outcomes of Fadama III among Fish Farmers in Nigeria: Evidence from Lagos State. (August 2019) - Alawode, O.O.; Oluwatayo, I.B.
Highlights: The first National Fadama Development Project (NFDP-1) was designed in the early 1990s to promote simple low-cost improved irrigation technology under World Bank financing. Fadama is a Hausa word which connotes low-lying and flood plain areas underlined by shallow aquifers and found along Nigeria's river system. The main objective of NFDP-1 was to sustainably increase the incomes of the Fadama users through expansion of farm and non-farm activities with high value-added output. NFDP adopted community driven development (CDD) approach with extensive participation of the stakeholders at early stage of the project. In 2004, having considered the success of the Fadama I programme, the Nigerian government launched the Second National Fadama Development Project (Fadama II) to increase the incomes of farmers and fishers in Fadama areas. Also, Fadama II sought to empower local communities and improve government's capacity to reach out specifically to the poor and vulnerable groups such as women, unemployed youth, widows, and people living with HIV/AIDS. The Fadama III programme started during the administration of Alhaji Umaru Yar'adua, with approval from July 2008 by the Worldbank (World Bank, 2014 ), the administration of President Goodluck Jonathan adopted the programme as one of the means of achieving agricultural transformation in Nigeria. NFDP III has a tripartite funding structure; the World Bank, the federal government and the participating states. It is being widely implemented in all the 36 states of the federation and the Federal Capital Territory (FCT), which have been categorized into the core states and the facility states. The core states include Bauchi, Gombe, Jigawa, Kano, Kebbi, Zamfara and Sokoto, while the remaining states and the FCT constitute the facility states. However, the main objective of the NFDP III is to sustainably increase the incomes of Fadama users, thereby helping to reduce rural poverty, increase food security and contribute to the achievement of a key millennium development goal – eradication of extreme poverty and hunger. Abstract: This paper is focussed on the analysis of development outcomes of Fadama III programme among fish farmers in Nigeria with evidence from Lagos state. Random sampling technique was used to select 141 fish farmers from the Fadama III participants and non-participants from three agricultural divisions. Data were collected through structured questionnaire and analysed using descriptive statistics. While propensity score matching approach was employed to estimate the Average Treatment Effect on the Treated (ATT) using productivity level as an outcome, double-difference approach and Gini coefficient were used to estimate the project's impact on the income of the beneficiaries. The double difference estimator showed that the fish farmers who participated in Fadama III programme had 62.4% increase in their income. Education level, income level before the programme and land ownership were factors that positively influenced the probability of participating in Fadama III. The ATT estimates showed that the intervention/programme had a positive impact on the production level of participants to the tune of 2.15 tonnes per year. The Gini coefficient also showed that the fish farmers were better-off as their Gini-index reduced from 0.755 to 0.489 after participation in Fadama III. Fish farming was found to be generally profitable in the study area with a net profit of ₦ 7.36 million per annum while the Benefit Cost (B/C) ratio was 3.95. The income of fish farmers, after participation in Fadama III project, was positively and significantly influenced by the occupation and income of the farmers before participation in the project. The beneficiaries/participants surpassed the target of 40% increase in income set for the project. The beneficiaries were therefore better-off after participating in the programme. It is recommended that other farmers having no access to large income should be encouraged to participate and be a part of the ongoing Fadama III additional financing initiative.